First discovery of the genus Enicopus Stephens (Coleoptera, Dasytidae) from China - Jialin Miao; Haoyu Liu; Junbo Tong; Xingke Yang; Yuxia Yang (Biodiversity Data Journal)
Enicopus Stephens, 1830, is classified within the subfamily Dasytinae of the family Dasytidae (Coleoptera, Cleroidea). Currently, it comprises two subgenera and 27 known species. This genus primarily inhabits south-central Europe, with certain species extending into west Asia; however, it has not been reported in China until now.The genus Enicopus Stephens, 1830 is reported for the first time from China, following the discovery of E. (Enicopus) ater (Fabricius, 1787) in Xinjiang Autonomous Region. This species is thoroughly re-described and illustrated, including detailed depictions of the ultimate abdominal tergites and sternites, genitalia of both sexes, as well as tarsomeres 1 from the right front and hind legs of male.